The impact of supervised and home exercise activity intervention on circulating immune cell numbers in cancer patients - Michal, Rihacek; Andrea, Wagnerova; Jana, Halamkova; Lucie, Pehalova; Eva, Rihackova; Lubos, Boucek; Kateřina, Kapounková; Iva, Hrnčiříková; Igor, Kiss (Heliyon, 2024)
INTRODUCTION: Malignant diseases challenge clinicians to balance treatment intensity and patient quality of life. Regular physical activity positively impacts mental and physical health, benefiting sleep patterns, heart rate, and overall health. Moreover, telehealth physical exercise training represents a viable option for maintaining intrinsic capacity. The American Cancer Society highlights exercise's role in helping patients cope with anti-cancer treatment side effects. In the Czech Republic, there is no fitness-promoting protocol for cancer patients, despite recognized benefits. Exercise may also enhance immune function, with moderate-intensity exercise potentially positively affecting immune cell counts. OBJECTIVE: This study aimed to analyze the long-term effects of exercise on circulating immune cells in patients undergoing treatment for solid malignancies. PATIENTS AND METHODS: 49 participants were recruited at the Masaryk Memorial Cancer Institute, Czech Republic, starting September 2021. Participants were randomized into an experimental (SAPA = undergoing monitored exercise program) group (N = 16; madian age: 46,6; median BMI: 25,1) and a control (CO) group (N = 33; madian age: 52,0; median BMI: 25,3). Flow cytometry was used to examine cellular immunological profiles. The exercise program involved thrice-weekly sessions conducted online. RESULTS: SAPA group showed stable lymphocyte counts post-exercise (percentage chance: +0,5 %; p = 0,256; effect size r = -0,284), while the CO group exhibited a significant drop (percentage chance: -23,0 %; p = 0,015; effect size r = -0,423). B lymphocyte numbers were significantly higher in the SAPA group post-exercise compared to the CO group (p = 0,003; effect size r = -0,422). The number of Th-lymphocytes, T-c lymphocytes, T-gamma/delta lymphocytes, and NK cells remained stable in SAPA but dropped in CO group. CONCLUSION: Exercise's impact on the immune system in cancer patients shows promise, with differences noted between acute and chronic exercise effects. Previous studies on acute exercise indicate a rise in immune cell counts, supporting our findings of stable or increased immune cells with controlled exercise in cancer patients. Controlled physical activity stabilizes or increases certain immune cell populations in patients undergoing chemotherapy for solid malignancies, highlighting the potential benefits of incorporating exercise into cancer treatment protocols.
Keywords: Chemotherapy; Oncology; Exercise; Fitness; Immune cells